The Impact of Promotion and Price on Purchase Decision Consumers at Marketplace Shopee - Alifian Sugeng Prasetyono; Joko Suyono; I Putu Artaya; Qausya Faviandhi (LPPM NAROTAMA UNIVERSITY, Indonesia, 2021)
All aspects of human life today use the internet, for example in the trade aspect. Based on these needs, various websites/applications have emerged that provide consumer goods. One such website/application is Shopee. This study focuses on purchasing decisions on the Shopee application. Purchasing decisions have several influencing factors, but researchers only take two factors, namely Promotion and Price. The purpose of this study was to analyze the effect of promotions and prices on purchasing decisions on the Shopee application/website. The approach in this study uses a quantitative approach, with the data collection technique is a questionnaire. This study used 100 respondents based on purposive sampling theory (respondents based on predetermined criteria). The data that has been collected through the distribution of the questionnaire will then be processed using multiple linear regression analysis techniques with the help of the SPSS program. The results of this study indicate that the Promotion and Price variables partially and simultaneously have a significant positive effect on the purchasing decision variables.